Prenatal stress, glucocorticoids and the programming of adult disease - Cottrell, Elizabeth C.; Seckl, Jonathan (Frontiers in Behavioral Neuroscience, 2009)
Numerous clinical studies associate an adverse prenatal environment with the development of cardio-metabolic disorders and neuroendocrine dysfunction, as well as an increased risk of psychiatric diseases in later life. Experimentally, prenatal exposure to stress or excess glucocorticoids in a variety of animal models can malprogram offspring physiology, resulting in a reduction in birth weight and subsequently increasing the likelihood of disorders of cardiovascular function, glucose homeostasis, hypothalamic-pituitary-adrenal (HPA) axis activity and anxiety-related behaviours in adulthood. During fetal development, placental 11β-hydroxysteroid dehydrogenase type 2 (11β-HSD2) provides a barrier to maternal glucocorticoids. Reduced placental 11β-HSD2 in human pregnancy correlates with lower birth weight and higher blood pressure in later life. Similarly, in animal models, inhibition or knockout of placental 11β-HSD2 lowers offspring birth weight, in part by reducing glucose delivery to the developing fetus in late gestation. Molecular mechanisms thought to underlie the programming effects of early life stress and glucocorticoids include epigenetic changes in target chromatin, notably affecting tissue-specific expression of the intracellular glucocorticoid receptor (GR). As such, excess glucocorticoids in early life can permanently alter tissue glucocorticoid signalling, effects which may have short-term adaptive benefits but increase the risk of later disease.